Pancreas Divisum: The Culprit or an Accomplice in Pancreatitis? - Kotha, Aasritha; Dontheneni, Shravya Bhargavi; Putta, Tharani; Peddapulla, Chandan; Talukdar, Rupjyoti (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The true causal relationship between pancreas divisum (PD) and pancreatitis is underexplored. Through this study, we aim to determine the prevalence and type of PD, and its association with idiopathic pancreatitis.We retrospectively reviewed all magnetic resonance cholangiopancreatographies (MRCPs) done in our center over 6 months (n = 2,762) for the presence and type of PD, acute or chronic pancreatitis, and any known etiology for pancreatitis. Statistical comparison was made between PD and non-PD groups using chi-square test for various demographic, clinical, and imaging parameters.PD was seen in 3.5% of MRCPs (98 out of 2,762) of which it was an incidental finding in 39%; 52% had idiopathic pancreatitis and 9% had other risk factor-associated pancreatitis (p < 0.00001). Idiopathic pancreatitis was found in 57.5, 52.5, and 44.5% of cases with type I PD (23/40), type II PD (21/40), and type III PD (8/18), respectively (p = 0.29). PD was demonstrated in 6.2% of patients with idiopathic pancreatitis (51/816) and 2.5% of patients with no pancreatitis (47/1848) (p = 0.0001), suggesting etiological relationship. However, there was no statistically significant difference in occurrence of idiopathic pancreatitis in patients with or without PD (85% vs. 76%, p = 0.5).Idiopathic pancreatitis is more prevalent in India compared with the West, despite the lower prevalence of PD. There is no difference in occurrence of idiopathic pancreatitis between PD and non-PD groups despite higher prevalence of PD in these patients, suggesting that PD by itself may not act as the sole cause of pancreatitis; it probably increases the susceptibility to idiopathic pancreatitis.
Keywords: pancreas divisum; idiopathic pancreatitis; magnetic resonance cholangiopancreatography; MRCP; recurrent acute pancreatitis